Some RNA Viruses - Shah, Yogendra; Abuelzein, Eltayb (IntechOpen, 2021)
This book provides an overview of the globally concerning and emerging public health RNA viruses like SARS-CoV2, Ebola virus, FMD disease, and others. The main drive to publish this book was to present information on the molecular epidemiology pattern, transmission dynamics, host response factor, RNA viral infection, RNA virus evolution, molecular biology of RNA viruses, pathogenesis mechanism and phylogenetic analysis causing viral diseases among humans. This book will help to provide updated research information to the policymaker or planner for further diagnosis with genotyping tools, control, and prevention for further outbreaks of diseases from RNA viruses in tropical and subtropical countries.